SISTEM INFORMASI PENCATATAN PRODUKSI PAKAIAN BERBASIS ANDROID - NURHASANDI, NURHASANDI; Turaina, Rifa; -, Sotar (JURNAL AKADEMIKA, 2024)
CV. Aya Sofya is a Muslim clothing manufacturer specializing in Gamis, Baju Koko, Kemeja Koko, Jilbab, Mukena, skirts, Civil Servant Office Uniforms, and more. Recognizing the need for efficiency, the company implemented an Android and web-based Information System. This system, developed with native Android and Codeigniter framework, streamlines quality control, warehouse operations, and administrative tasks. Following the System Development Life Cycle with the Waterfall model, and aided by Unified Modeling Language (UML), the manual production recording process has been replaced, significantly enhancing effectiveness and efficiency. The frontend on Android allows quality control to record production activities seamlessly. Meanwhile, the web-based backend aids warehouse operators in tracking raw materials and assists administrators with payroll and report generation. This research underscores how the Information System has effectively optimized production activities for quality control, warehouse operations, and administration at CV. Aya Sofya.